Scoliosis among children in Qinghai-Tibetan Plateau of China: A cross-sectional epidemiological study - Zhou, Lijin; Yang, Honghao; Hai, Yong; Hai, Junrui Joanthan; Cheng, Yunzhong; Yin, Peng; Yang, Jincai; Zhang, Yangpu; Wang, Yunsheng; Zhang, Yiqi; Han, Bo (Frontiers in Public Health, 2022)
Background The average altitude of Qinghai-Tibetan Plateau is 4,500 m and most of the residents are Tibetan ethnicity. The purpose of this study was to investigate the prevalence of scoliosis and associated factors among children in this region through a scoliosis screening program. Methods A cross-sectional study was preformed between May 2020 and December 2020 in Qinghai-Tibetan Plateau. A total of 9,856 children aged 6–17 years from schools and nearby villages were screened using visual inspection, the Adams forward-bending test, the angle of trunk rotation, and radiography. A self-designed questionnaire was used to collect demographic data. The prevalence of scoliosis and associated factors were analyzed. Results The overall prevalence of scoliosis among children in Qinghai-Tibetan Plateau was 3.69%, with 5.38% for females and 2.11% for males. The prevalence of scoliosis was 3.50% in children resided below 4,500 m while 5.63% in those resided above 4,500 m (P = 0.001). The prevalence of congenital scoliosis (2.14 vs. 0.42%, P < 0.001) and neuromuscular scoliosis (0.34 vs. 0.07%, P = 0.041) were significantly higher in the altitude above 4,500 m. 50.00% of patients resided above 4,500 m were recommended for surgery while 16.24% in those resided below 4,500 m (P < 0.001). Independent associated factors were detected as female (OR = 2.217, 95 CI% 1.746–2.814, P < 0.001), BMI < 18.5 (OR = 1.767, 95 CI% 1.441–2.430, P = 0.005), altitude of residence ≥ 4,500 m (OR = 1.808, 95 CI% 1.325–2.483, P = 0.002), and sleep time < 8 h (OR = 2.264, 95 CI% 1.723–2.846, P = 0.001). Conclusion The prevalence of scoliosis among children in Qinghai-Tibetan Plateau was 3.69%. With increasing altitudes, the prevalence of scoliosis and its major type were different from that at lower altitudes. Female, BMI < 18.5, altitude of residence ≥ 4,500 m, and sleep time < 8 h were independently associated with the prevalence of this disease. Early screening should be carried out before the age of 7 years, especially in the high-altitude, underdeveloped, and rural areas.